2017
DOI: 10.1001/jamainternmed.2017.3941
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Testing and Treatment for Latent Tuberculosis Infection in Residents Born Outside the United States With and Without Medical Comorbidities in a Simulation Model

Abstract: IMPORTANCE Testing for and treating latent tuberculosis infection (LTBI) is among the main strategies to achieve TB elimination in the United States. The best approach to testing among non-US born residents, particularly those with comorbid conditions, is uncertain.OBJECTIVE To estimate health outcomes, costs, and cost-effectiveness of LTBI testing and treatment among non-US born residents with and without medical comorbidities. DESIGN, SETTING, AND PARTICIPANTS Decision analytic tree and Markov cohort simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(101 citation statements)
references
References 35 publications
2
98
0
1
Order By: Relevance
“…However, available resources for TB prevention programs remain limited, which highlights the need to ensure that TB testing programs are as cost-effective as possible. Tasillo et al demonstrated the cost-effectiveness of testing and treating LTBI among non-US-born persons (31). Our analysis emphasizes the value of focusing on country of birth and length of time in the United States to guide how to best expand LTBI testing and treatment.…”
mentioning
confidence: 85%
“…However, available resources for TB prevention programs remain limited, which highlights the need to ensure that TB testing programs are as cost-effective as possible. Tasillo et al demonstrated the cost-effectiveness of testing and treating LTBI among non-US-born persons (31). Our analysis emphasizes the value of focusing on country of birth and length of time in the United States to guide how to best expand LTBI testing and treatment.…”
mentioning
confidence: 85%
“…Expanded treatment of LTBI will be required to reduce the TB incidence further. The use of IGRA for diagnosis and rifamycin‐based regimens for treatment of LTBI appears to be a cost‐effective community intervention for immigrants in the US, both with and without medical risks for progression . In Japan, mandatory reporting of LTBI may facilitate the evaluation of country‐level strategies that could help inform strategies in the US and elsewhere …”
Section: The Challenge Of Implementing National Tb Elimination Plansmentioning
confidence: 99%
“…The use of IGRA for diagnosis and rifamycin-based regimens for treatment of LTBI appears to be a cost-effective community intervention for immigrants in the US, both with and without medical risks for progression. 70 In Japan, mandatory reporting of LTBI may facilitate the evaluation of country-level strategies 71 that could help inform strategies in the US and elsewhere. 67,71 For countries with an intermediate or higher TB incidence, implementing effective LTBI treatment programmes represents both a challenge and opportunity.…”
Section: The Challenge Of Implementing National Tb Elimination Plansmentioning
confidence: 99%
“…As noted by the authors, the assumptions of this study differ from previous studies, [4][5][6] including our own, which reported that LTBI screening and treatment for immigrant patients with CKD would be cost prohibitive, with associated incremental cost-effectiveness ratios in the hundreds of thousands of dollars. These discrepancies underscore the importance of health care system context when making decisions.…”
Section: Related Article P 39mentioning
confidence: 71%